Overweight and obesity among urban women with iron deficiency anaemia in Bangladesh - Nazia Binte Ali; Michael J. Dibley; Sajia Islam; Mohammad Masudur Rahman; Shahreen Raihana; Shams E. Tabriz Bhuiyan; Qazi Sadequr Rahman; Hafizur Rahman; Shams El Arifeen; Tanvir M. Huda (Wiley, 2021)
Abstract In this study, we aimed to determine the prevalence and factors associated with overweight and obesity among nonpregnant and nonlactating (NPNL) women of reproductive age with iron deficiency anaemia (IDA) in urban Bangladesh. We obtained data from the baseline assessment of a randomized control trial conducted among 525 women of reproductive age (18-49 years) with IDA (Hb < 12 gdl−1 and serum ferritin <30 μg L−1). The study was carried out in Mirpur, Dhaka, Bangladesh, between December 2017 and January 2019. We collected information on women's socio‐demographic characteristics and anthropometry. Body mass index (BMI) was calculated using the following formula: weight in kilograms per height in square metres. BMI ≥ 25-29.9 kg m−2 was considered as overweight, whereas BMI ≥ 30 kg m−2 as obese. A multivariable logistic regression model was used to ascertain the risk factors of overweight and obesity. The prevalence of overweight and obesity was 29.9% (95% CI: 26.0-34.0) and 13.1% (95% CI: 10.4-16.3), respectively. The combined prevalence of overweight and obesity was 43.0% (95% CI: 38.7-47.4). The multivariable analysis showed married women (aOR: 4.4; CI: 1.8-11.1), women aged 30-49 years (aOR: 7.6; CI: 2.4-24.1), unemployed women (aOR 1.5; CI: 1.0-2.4) and women from the wealthier households (aOR 3.9; CI: 2.3-6.8) had the highest risk of being overweight and obese compared with their counterparts. Both age and household wealth statuses showed dose-response relationships. Combination of overweight and obesity with IDA poses a particular challenge for public health interventions. The policymakers should consider what new interventions and policy initiatives are needed to address this combination of overweight and obesity with IDA.